Mentality and Mindset as Categories of Sociocultural and Civilizational Anthropology - Yurii, Mykhailo; Khrystan, Nazarii (Mediaforum : Analytics, Forecasts, Information Management, 2023)
The article examines the content and mechanism of the interaction of mentality and mentality as phenomena of the spiritual and mental life of an ethnic group, a people. The relevance of intelligence is determined by the fact that the tradition of understanding them as synonymous is preserved in scientific research, but at this stage these concepts are becoming more and more controversial. Mentality is a scientific category that reflects a certain phenomenon that is rooted in the depths of people’s life and captures stable, established characteristics of spirituality. Anthropology records the constancy of mentality, its staticity, but at the same time its relative changeability, because it is a mechanism that determines the reaction to the surrounding world. In the terminology of anthropologists, mentality is expressed through the concept of «general instructions» associated with behavioral characte-ristics, which at the same time does not depend on conscious reflection. In other words, mentality can be understood as a system of relatively strong stereotypes, as it necessarily reflects certain static properties of a social type that have developed in the process of life experience. As for mentality, it is a qualitative, identifying characteristic of a social subject that focuses natural-historical and cultural features in itself. The definition of mentality and mentality, their differences, is substantiated on the basis of historiographical research of foreign and domestic scientists, scientific schools of sociology, cultural studies and psychology.